What About the Neuroimaging Findings in Social Anxiety Disorder? - Atmaca, Murad (Bentham Science Publ Ltd, 2013)
In the present article, structural, neurochemical and functional neuroimaging investigations performed on patients with social anxiety disorder were reviewed. A PubMed search was performed to identify all structural and functional neuroimaging studies published between 1980 and February 2013. The studies and case reports on neuroimaging in social anxiety disorder were grouped under the subheadings of structural, functional and magnetic resonance spectroscopic imaging. It seems that structural studies involve examination of abnormalities in the basal ganglia structures like caudate nucleus, thalamus, and putamen, hippocampus and amygdala abnormalities in summary. Neurochemical investigations reveal the deficiencies in the GABAergic system and over-activation in the glutamatergic system in social anxiety disorder. Functional neuroimaging investigations implicate the role of limbic-medial prefrontal circuit.
Keywords: Social anxiety disorder; neuroimaging; structural; functional; MRI